Mining, modeling, and recommending 'things' in social media : 4th International Workshops, MUSE 2013, Prague, Czech Republic, September 23, 2013, and MSM 2013, Paris, France, May 1, 2013, Revised selected papers /: 4th International Workshops, MUSE 2013, Prague, Czech Republic, September 23, 2013, and MSM 2013, Paris, France, May 1, 2013, Revised selected papers. (2015) - Unknown
No abstract available